Crohn’s disease - diagnosis and treatment - Ręba, Patrycja (Journal of Education, Health and Sport, 2021)
Admission Crohn’s disease belongs to the group of chronic and still incurable diseases. It has periods of exacerbation and partial or complete remission. It mainly affects young people. The peak incidence is between the ages of 15 and 35, but it is possible to develop the first symptoms of the disease at any age. Due to its chronicity, incurability and the possibility of various complications, this disease is a heavy psycho-physical as well as social burden. Aim The aim of the study is to analyze the diagnosis and treatment of Crohn’s disease. Material and method Review of the available literature on the subject. Results Crohn’s disease is a disease that may affect any part of the gastrointestinal tract (most often the end segment of the small intestine), causing a significant reduction in the quality of life and impairment of the patient’s efficiency. The most common symptoms are abdominal pain, diarrhea, blood in the stools, testable (often tender) abdominal resistance, weight loss, weakness, low-grade fever, and fever. They are often accompanied by changes in the anal area - fistulas, fissures and abscesses, as well as entero-skin fistulas. Diagnosis is based on endoscopy with biopsy, histopathology and radiological methods using contrast. Despite better recognition and easier access to diagnostics, some cases are diagnosed during the procedure due to obstruction or misdiagnosed appendicitis. The most commonly used treatments are 5-aminosalicylates, glucocorticosteroids and thiopurines. Currently, two anti-TNF-α antibodies used in biological therapy are registered in Poland. Conclusions Treatment with classical methods and biological drugs does not always avoid surgical intervention. Long-term observation shows that most patients undergo at least one surgery. New reports more and more boldly indicate the desirability of early introduction of biological and immunosuppressive therapy (top-down strategy). Although the chance of disease change as a result of aggressive treatment from the moment of diagnosis is tempting, due to the possible complications of such therapy, especially infectious, caution should be exercised until we have more data. These complications also require that this treatment be dealt with by reference centers with extensive experience in this field.